FEATURES OF THE LANGUAGE OF ESSAYS IN THE NEWSPAPERS "VOICE OF TAJIK" AND "VOICE OF SAMARKAND - Равзатуллоева Сония Фарҳод қизи (Bright Mind Publishing, 2025)
This article provides information about the origin of the Tajik language and its formation and development. The contribution of newspapers and magazines to the development of the Tajik language is of particular importance, and this topic is discussed in separate sections, and the peculiarities of the language of essays in the newspapers "Ovozi Samarkand" and "Ovozi Tojik" are analyzed and discussed.
Keywords: Language, newspaper, magazine, essay, uniqueness, eloquence, fluency, simplicity, Rudaki, native language, “Voice of the Tajik”, “Voice of Samarkand”, literary genre, publicism.